2015
DOI: 10.1117/1.jbo.20.8.085003
|View full text |Cite
|
Sign up to set email alerts
|

Use of optical skin phantoms for preclinical evaluation of laser efficiency for skin lesion therapy

Abstract: Abstract. Skin lesions are commonly treated using laser heating. However, the introduction of new devices into clinical practice requires evaluation of their performance. This study presents the application of optical phantoms for assessment of a newly developed 975-nm pulsed diode laser system for dermatological purposes. Such phantoms closely mimic the absorption and scattering of real human skin (although not precisely in relation to thermal conductivity and capacitance); thus, they can be used as substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The findings of the experimental results that we presented are relevant to cylindrical tissues such as fingertip, earlobe, lips or any pinched tissue. It can be useful for detecting physiological states using the different optical properties in the different states, like changes in the blood vessel diameters or the changes in skin scattering upon laser treatment [26,27] that influences the full scattering profile. This new technique can be implemented in various optical methods such as NIR spectroscopy [28,29] PPG experiments, and improves analyzing of oxygen saturation values, blood perfusion and blood pressure.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of the experimental results that we presented are relevant to cylindrical tissues such as fingertip, earlobe, lips or any pinched tissue. It can be useful for detecting physiological states using the different optical properties in the different states, like changes in the blood vessel diameters or the changes in skin scattering upon laser treatment [26,27] that influences the full scattering profile. This new technique can be implemented in various optical methods such as NIR spectroscopy [28,29] PPG experiments, and improves analyzing of oxygen saturation values, blood perfusion and blood pressure.…”
Section: Resultsmentioning
confidence: 99%
“…They serve as reference standards for comparison of devices and techniques as well as for studying light transport in complex, often multi-layered tissues or organs with internal vasculature [10,11]. Also phantom studies of nanoparticles for skin cancer diagnosis and laser therapy has been reported [12,13]. A multitude of different types of phantoms have been invented to suit the needs of specific research methods, such as fluorescence [14] or Raman [15] imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The investigations show a variety of advanced biomedical technologies, which are in direct need of knowledge of the optical parameters of tissues. As the most impressive and useful examples of tissue quantified data application, there are the dosimetry of radiation during PDT and PTT 27,28 and in laser surgery, 29 various imaging technologies, 1,2,19,[30][31][32][33][34][35][36][37][38][39][40] the development of batteryless solar-powered cardiac pacemakers, 41 standardization of tissue-mimicking phantoms, 32,[42][43][44][45][46] assessment of tissue chromophore concentration and distribution, 47,48 and proposition of adequate optical models of tissues. [49][50][51][52] This paper gives an overview of recent results on the measurements and control of tissue optical properties that were presented on the VI International Symposium "Topical Problems of Biophotonics 2017," St.-Petersburg, Nizhny Novgorod, Russia, July 28 to August 03, 2017, as an invited talk.…”
Section: Introductionmentioning
confidence: 99%